VEILING: Between Social Imaginary and the Politic of Multiculturalism In Indonesia and Malaysia - Sunesti, Yuyun (Sunan Kalijaga State Islamic University & The Asia Foundation, 2016)
Hijab (veiling) becomes a social imagination of piety for many muslim women. In Many areas in Indonesia, veiling even becomes one of the points of obligation in local regulations. This article discusses the social imaginary about the hijab for muslim women in Indonesia and Malaysia which then transforms into a social obligation supported by the state. The fact that these two countries run the multicultural politics that is required for accommodating religious, racial, and cultural differences is a challenge when the efforts of homogenizing identity continue to be fought by certain groups.[Jilbab menjadi imajinasi sosial tentang kesalehan bagi banyak perempuan muslim. Di banyak daerah di indonesia, berjilbab bahkan menjadi salah satu kewajiban yang masuk dalam peraturan daerah. Artikel ini membahas tentang imajinasi sosial (social imaginary) tentang jilbab bagi perempuan muslim di Indonesia dan Malaysia yang selanjutnya bertransformasi menjadi kewajiban sosial (social obligation) yang didukung oleh negara. Fakta bahwa kedua negara ini menjalankan politik multikulturalisme yang dituntut untuk mengakomodasi perbedaan agama, ras, dan budaya menjadi tantangan tersendiri ketika upaya-upaya homogenisasi indentitas terus diperjuangkan oleh kelompok-kelompok tertentu.]